Dayside Magnetospheric and Ionospheric Responses to a Foreshock Transient on 25 June 2008: 2. 2‐D Evolution Based on Dayside Auroral Imaging. Issue 8 (15th August 2018) - Wang, Boyi; Nishimura, Yukitoshi; Hietala, Heli; Shen, Xiao‐Chen; Shi, Quanqi; Zhang, Hui; Lyons, Larry; Zou, Ying; Angelopoulos, Vassilis; Ebihara, Yusuke; Weatherwax, Allan
Abstract: The foreshock region involves localized and transient structures such as foreshock cavities and hot flow anomalies due to solar wind‐bow shock interactions, and foreshock transients have been shown to lead to magnetospheric and ionospheric responses. In this paper, the interaction between a foreshock transient and the magnetosphere‐ionosphere system is investigated using dayside aurora imagers revealing structures and propagation in greater detail than previously possible. A foreshock transient was detected by Time History of Events and Macroscale Interactions during Substorms B and C during 1535–1545 UT on 25 June 2008. Time History of Events and Macroscale Interactions during Substorms A, D, and E observed magnetopause compression, cold plasma enhancement, and ultralow frequency waves in the dayside magnetosphere. The all‐sky imager at South Pole observed that both diffuse and discrete aurora brightened locally soon after the appearance of this foreshock transient. The diffuse aurora brightening, which corresponded to a region a few Re size in geocentric solar magnetospheric Y in the equatorial plane, propagated duskward with an average speed of ~100 km/s. Soon after the diffuse aurora brightened, discrete aurora also brightened and extended duskward, which was consistent with the motion of the foreshock transient as it swept through the magnetosheath while impacting the magnetopause. Equivalent horizontal currents measured by magnetometers revealed a pair of field‐aligned currents moving duskward consistent with motion of the discrete aurora patterns. We conclude that the high‐resolution and two‐dimensional observation of auroral responses by ground‐based all‐sky imager can help to estimate the evolution and propagation of upstream foreshock transients and their substantial impacts on the magnetosphere‐ionosphere coupling system, including magnetospheric compression and currents in the ionosphere. Key Points: We, for the first time, show auroral evolution due to a foreshock transient in high‐resolution 2‐D imaging By mapping to the magnetosphere, the imaging was able to determine the size (a few Re in Y) and propagation (duskward) Equivalent currents show a pair of FACs. Its duskward propagation is consistent with aurora. The response resembles sudden commencements